2020
DOI: 10.1021/acsanm.0c02062
|View full text |Cite
|
Sign up to set email alerts
|

Quaternized Cationic Carbon Dots as Antigen Delivery Systems for Improving Humoral and Cellular Immune Responses

Abstract: The current licensed adjuvant alum is found to be insufficient to induce cellular immune responses and a balanced Th1/Th2 ratio, which are desirable against cancers and microbial infections. Hence, it is encouraged to develop adjuvants which can simultaneously improve cell-mediated and humoral immune responses of the antigen and possess a favorable Th1/ Th2 balance. Herein, quaternized cationic carbon dots derived from biquaternary ammonium salt (BQAS-CDs) were newly prepared, and their adjuvanticity and bioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…The fluorescence intensity of JB-CDs decreased a little (Figure S4c) as the temperature was varied from 20 to 80 °C, indicating that the temperature had little influence on the emission. A similar type of observation was also stated by Huang et al and Yang et al The fluorescence intensity of JB-CDs maintains more than 98% of its original intensity after 45 days of storage at 4 °C (Figure f). For long periods of storage, the JB-CD solution can be dried in a vacuum oven to acquire their powder, which were redispersed in water before use.…”
Section: Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The fluorescence intensity of JB-CDs decreased a little (Figure S4c) as the temperature was varied from 20 to 80 °C, indicating that the temperature had little influence on the emission. A similar type of observation was also stated by Huang et al and Yang et al The fluorescence intensity of JB-CDs maintains more than 98% of its original intensity after 45 days of storage at 4 °C (Figure f). For long periods of storage, the JB-CD solution can be dried in a vacuum oven to acquire their powder, which were redispersed in water before use.…”
Section: Results and Discussionsupporting
confidence: 87%
“…This phenomenon might be accredited to the different protonation degreed of different functionalities at different pHs. In the low pH range, the low fluorescence response was caused by the protonation of surface functional groups; while in the basic condition, JB-CDs were converted to an electronegative form resulting in partial aggregation of JB-CDs. This aggregation of JB-CDs might be due to the result of physical interactions, , causing a gradual decrement in the fluorescence response at basic pH.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In a previous study, Huang et al . reported that quaternate cationic CQDs could act as an adjuvant to promote antigen presentation and induce robust immune response [ 204 ]. In this study, the positively charged CQDs were synthesized from hydrothermal method using bi-quaternary ammonium salt (BQAS) as raw material.…”
Section: Application Of Carbon Quantum Dots For Inhibition and Treatm...mentioning
confidence: 99%
“…B Percentage of positive BMDC cells after incubating with OVA and OVA conjugated CDs. C ELISA result of IgG concentration in sera of BALB/c mice intramuscularly immunized with different adjuvants: BQAS, alum, or CQDs [ 204 ]. Reproduced with permission.…”
Section: Application Of Carbon Quantum Dots For Inhibition and Treatm...mentioning
confidence: 99%
“…The subsequent interaction of ions or molecules can modify the localized surface states, thus causing a photoluminescence quenching or enhancement effect. As a consequence, these materials are promising candidates for replacing the metal-based quantum dots in various applications, such as bioimaging [ 11 , 12 , 13 ], biosensing [ 14 , 15 ], drug delivery [ 16 , 17 ], adjuvant selection in vaccines [ 18 ], and photocatalysis [ 19 ]. The working mechanism in sensing and imaging applications is related to the presence of functional groups, which can coordinate the metals being detected, thus affecting the optical properties.…”
Section: Introductionmentioning
confidence: 99%